The shadows of poetry : Vergil in the mind of Augustine - MacCormack, Sabine (University of California Press, 1998)
Imperial ceremony was a vital form of self-expression for late antique society. Sabine MacCormack examines the ceremonies of imperial arrivals, funerals, and coronations from the late third to the late sixth centuries A.D., as manifest in the official literature and art of the time. Her study offers us new insights into the exercise of power and into the social, political, and cultural significance of religious change during the Christianization of the Roman w.
Earlier versions of three chapters were presented as a Christian Gauss Seminar in Criticism, Princeton University, winter of 1994.
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Virgil.; Augustine, -- of Hippo, Saint, -- 354-430 -- Literary style.; Virgil -- Influence.; Augustine, -- of Hippo, Saint, -- 354-430 -- Books and reading.; Augustine, -- Saint, Bishop of Hippo.; Augustine, -- of Hippo, Saint, -- 354-430; Virgil; RELIGION -- Christian Church -- History.; RELIGION -- Christianity -- History.; Influence (Literary, artistic, etc.); Literary style; Religion.; Philosophy & Religion.; Christianity.